2022
DOI: 10.1039/d2ra03995h
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental understanding of the size and surface modification effects on r1, the relaxivity of Prussian blue nanocube@m-SiO2: a novel targeted chemo-photodynamic theranostic agent to treat colon cancer

Abstract: A targeted multimodal strategy on a single nanoplatform is attractive in the field of nanotheranostics for the complete ablation of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…Herein, it may be stated that T IS 1M consists of two different interactions, namely scalar (T SC 1 ) and dipole-dipole (T DD 1 ), ascribed to electronic and nuclear interactions between H 2 O protons and as-synthesized nanocubes, but we found that T 1M c T DD 1 , whereas the Curie spin relaxation mechanism dominates T 2M . 16,49 Moreover, it was reported earlier that the electronic relaxation time (t e ) is inconsiderable at a high magnetic field (B3 T) and t m c t R , which indicates t ci , t cs E t R , where t ci (i = 1, 2) and t cs denote magnetic fluctuation time and Curie spin correlation time. 16,50 Herein, t R , t ci (i = 1, 2) and t cs denote rotational correlation time, magnetic fluctuation time and Curie spin correlation time.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Herein, it may be stated that T IS 1M consists of two different interactions, namely scalar (T SC 1 ) and dipole-dipole (T DD 1 ), ascribed to electronic and nuclear interactions between H 2 O protons and as-synthesized nanocubes, but we found that T 1M c T DD 1 , whereas the Curie spin relaxation mechanism dominates T 2M . 16,49 Moreover, it was reported earlier that the electronic relaxation time (t e ) is inconsiderable at a high magnetic field (B3 T) and t m c t R , which indicates t ci , t cs E t R , where t ci (i = 1, 2) and t cs denote magnetic fluctuation time and Curie spin correlation time. 16,50 Herein, t R , t ci (i = 1, 2) and t cs denote rotational correlation time, magnetic fluctuation time and Curie spin correlation time.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…16,49 Moreover, it was reported earlier that the electronic relaxation time (t e ) is inconsiderable at a high magnetic field (B3 T) and t m c t R , which indicates t ci , t cs E t R , where t ci (i = 1, 2) and t cs denote magnetic fluctuation time and Curie spin correlation time. 16,50 Herein, t R , t ci (i = 1, 2) and t cs denote rotational correlation time, magnetic fluctuation time and Curie spin correlation time. Based on these approximations, r IS 1 and r IS 2 can be further simplified as follows:…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we developed erythrocyte and HCT116 cancer cell hybrid membrane-cloaked ROS-responsive nanoparticles to obtain a biomimetic nanocarrier co-encapsulating oxaliplatin (Oxa) and chlorin e6 (Ce6) (denoted as hNPOC) for chemophotodynamic synergistic therapy of colon cancer. As shown in Figure , the RBC membrane (rM) and cancer cM were separately obtained from respective erythrocytes and HCT116 cells and then fused together to form an RBC-HCT116 hybrid membrane. The nanoparticle cargo was fabricated by utilizing a reactive oxygen species (ROS)-responsive polyphosphoester (Figure S1, TK-PPE, containing extensive thioketal bond) to co-encapsulate Oxa and Ce6 (denoted as NPOC) according to the nanoprecipitation method.…”
Section: Introductionmentioning
confidence: 99%